Neuronal lactate levels depend on glia‐derived lactate during high brain activity in Drosophila. Issue 6 (26th December 2019) - González‐Gutiérrez, Andrés; Ibacache, Andrés; Esparza, Andrés; Barros, Luis Felipe; Sierralta, Jimena
Abstract: Lactate/pyruvate transport between glial cells and neurons is thought to play an important role in how brain cells sustain the high‐energy demand that neuronal activity requires. However, the in vivo mechanisms and characteristics that underlie the transport of monocarboxylates are poorly described. Here, we use Drosophila expressing genetically encoded FRET sensors to provide an ex vivo characterization of the transport of monocarboxylates in motor neurons and glial cells from the larval ventral nerve cord. We show that lactate/pyruvate transport in glial cells is coupled to protons and is more efficient than in neurons. Glial cells maintain higher levels of intracellular lactate generating a positive gradient toward neurons. Interestingly, during high neuronal activity, raised lactate in motor neurons is dependent on transfer from glial cells mediated in part by the previously described monocarboxylate transporter Chaski, providing support for in vivo glia‐to‐neuron lactate shuttling during neuronal activity. Abstract : We characterize lactate/pyruvate transport in glial cells and neurons from Drosophila larval brain using FRET sensors. Raises in neuronal lactate during high neuronal activity is dependent on the transfer of monocarboxylates from glial cells.